Long term survival and outcomes in patients with paraneoplastic neurologic syndromes - Bar Mucha, Sapir; Rozenberg, Ayal; Gutter Kapon, Lilach; Gorenshtein, Alon; Ganelin-Cohen, Esther; Ben Hayun, Rachel; Yarovinsky, Nataliya; Shelly, Shahar (Frontiers in Immunology, 2024)
ObjectiveIt is unknown whether delay in diagnosis affects morbidity reportedly in paraneoplastic syndromes (PNS). We aimed to explore various aspects of PNS, including prevalence, clinical characteristics, diagnostic criteria, and treatment outcomes.MethodsWe studied n-PNS diagnosis between 2016 to 2023, and included only patients with positive onconeural antibodies, who developed cancer, and exhibited a recognizable PNS phenotype.ResultsWe identified 12 patients with positive Abs and co-occurring cancer, most prevalent PNS antibodies included anti-GAD65, anti-Recoverin and anti-Yo. The most common phenotypes were limbic encephalitis (n=5, 42%) and encephalomyelitis (n=4,33%). Cancer preceded neurological presentation in 6 cases. Among the 6 patients who initially presented with n-PNS, median time from neurological presentation to oncologic diagnosis was 73 days, as five of them (83%) were diagnosed with cancer during oncological evaluation prompted by the PNS diagnosis or suspicion. Lymphoma was the most frequent cancer (n=3, 25%), followed by lung cancer (n=2, 17%), and ovarian cancer (n=2, 17%). Among patients who received immunotherapy as n-PNS treatment (n=9, 75%), steroids were a part of the management at 78% (n=7). Another immunotherapy used included plasmapheresis (n=5, 55%) and steroid sparing immunosuppressant (n=2, 29%). Four (33%) patients had short term therapeutic benefit with improvement or stabilization at mRS ≤ 4. Median Disability-adjusted life years (DALYs), as disease burden value, was 13 years. Death occurred in 9 of the 12 patients, with most cases deaths attributed to cancer progression. Compering to the expected median survival by type and stage of tumor, from 9 deceased patients, 56% (n=5) died younger than expected. Median survival was 410 days (range 29-2738 days), and 152 days since the appearance of n-PNS (range 8-1434 days). There were no differences in survival between patients who initially presented with n-PNS versus cancer (p=0.39).ConclusionIn up to 8 years of follow up, there was no difference in mortality among patients who presented initially n-PNS. There was a significant decline in the quality of life, most face substantial disability and functional impairment long term.